Changes in milk fat globule membrane proteins along lactation stage of Laoshan dairy goat - Chuozi Liang; Zhongna Yu; Guangming Zhu; Yixuan Li; Xueheng Sun; Hongning Jiang; Qijing Du; Rongbo Fan; Jun Wang; Yongxin Yang; Rongwei Han (Journal of Integrative Agriculture, 2024)
The milk fat globule membrane (MFGM) is a complex structure with numerous functions, and its composition is affected by many factors. There have been few systematic investigations on goat MFGM proteome profiling during lactation. Individual milk samples from 15 healthy dairy goats were obtained at six lactation time points for investigation of the MFGM proteome using both data-independent acquisition (DIA) and data-dependent acquisition (DDA) proteomics techniques combined with multivariate statistical analysis. Using the DIA method, 890 variably abundant MFGM proteins were discovered throughout the lactation cycle. From 1 to 240 d, butyrophilin subfamily 1 member A1, lipoprotein lipase, perilipin-2, and adipose triglyceride lipase were upregulated, while APOE, complement C3, clusterin, and IgG were downregulated. Furthermore, from 1 to 90 d, annexin A1, annexin A2, and antithrombin-III were downregulated, then upregulated by d 240. Albumin had a high degree of connectedness, indicating that it was a key protein, according to protein–protein interaction research. Overall, our findings gave new insights into the biological features of MFGM protein in goat milk throughout lactation, which may aid in the creation of specialized MFGM products and infant formula.